Histology and ultrastructure of pericardial cells of Scaptotrigona postica latreille (Hymenoptera, Apidae) in workers and queens of different ages - Poiani, Silvana Beani; da Cruz-Landim, Carminda (Elsevier B.V., 2007)
The paper presents a study of the pericardial cells of Scaptotrigona postica an eusocial Brazilian stingless bee. Light and electron microscopy was used in a comparative study on workers and queens of different ages, exerting different functions in the colony. The pericardial cells are found only in the peticardial sinus, mainly in groups around the dorsal vessel. Each cell is enclosed by the basal membrane and its peripheral region is characterized by folds of the plasma membrane, which form canals and loops. The points where the plasma membrane folds is frequently closed by diaphragms, that along with the basal lamina form a barrier to substances from hemolymph. Along the membrane limiting the canals and loops, an intense endocytic activity through coated vesicles takes place indicating a selective absorption of hemolymph components. In older individuals, workers or queens, the cells exhibit larger quantities of cytoplasm inclusions, heterogeneous vacuoles containing the final products of intracellular digestion, and autophagic vacuoles with concentric membranous structures. The pericardial cells general morphology is in accordance with the role in processing metabolites captured from hemolymph and storage of indigested residues. (C) 2006 Elsevier Ltd. All rights reserved.
Keywords: insect; bee; morphology; pericardial cell; nephrocyte; coated vesicles; senescence